2014
DOI: 10.4155/fmc.14.120
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Sh2 Domains in Breast Cancer

Abstract: Breast cancer is among the most commonly diagnosed cancer types in women worldwide and is the second leading cause of cancer-related disease in the USA. SH2 domains recruit signaling proteins to phosphotyrosine residues on aberrantly activated growth factor and cytokine receptors and contribute to cancer cell cycling, metastasis, angiogenesis and so on. Herein we review phosphopeptide mimetic and small-molecule approaches targeting the SH2 domains of Grb2, Grb7 and STAT3 that inhibit their targets and reduce p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 114 publications
(130 reference statements)
0
49
0
Order By: Relevance
“…A number of strategies have been examined to inhibit STAT3 activation, such as targeting the activating JAK2 kinase; however, these broad-spectrum approaches often result in off-target effects [10, 12, 14, 15]. Therefore, there has been recent interest in direct inhibition of STAT3, and this has mainly focused on targeting the SH2 dimerization domain [14, 16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of strategies have been examined to inhibit STAT3 activation, such as targeting the activating JAK2 kinase; however, these broad-spectrum approaches often result in off-target effects [10, 12, 14, 15]. Therefore, there has been recent interest in direct inhibition of STAT3, and this has mainly focused on targeting the SH2 dimerization domain [14, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there has been recent interest in direct inhibition of STAT3, and this has mainly focused on targeting the SH2 dimerization domain [14, 16]. The SH2 domain is the location of the activating Tyr705 residue and is the protein-protein interface responsible for the formation of transcriptionally active STAT3 dimers (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The p ‐chlorobenzyl group (region B, Figure ) was retained unmodified in most compounds as it is involved in key interactions via a π–π stacking with the aromatic side chain of Tyr 925. The salicylate aromatic moiety replacing the pyridine ring was reported to mimic the phosphorylated tyrosine (pTyr) . Molecular modelling studies of the newly designed compounds showed improved binding interaction modes within the FAK‐FAT pocket compared to the parent C4 compound due to a better orientation effect on the side chain (region C, Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…For certain tumors, the sustained activation of STAT3 resulted in the enhancement of activation of EGFR signal transduction pathways (57). STAT3 binds to activated EGFR via SH2 domains; stimulation of EGFR induces Tyr705 phosphorylation of STAT3, which is a prerequisite for dimerization of STATs, which again occurs via the SH2 domains (58). The dimerization of tyrosine-phosphorylated STATs leads to their nuclear accumulation, DNA binding at specific sites and the transcriptional activation of target genes (57).…”
Section: Discussionmentioning
confidence: 99%